1991
DOI: 10.1002/jso.2930480204
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in laryngeal cancer patients submitted to surgical treatment

Abstract: The authors studied some demographic, clinical, pathologic, and therapeutic variables in relation to the disease-free interval (DFI) and to the overall survival of laryngeal cancer patients. The patient population consisted of 278 consecutive cases of primary laryngeal cancer who had been admitted to four head and neck surgery services in Sao Paulo and Curitiba (Brazil) between 1973 and 1986. All patients had surgical treatment. Although several variables exhibited individual associations with survival, only a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
2
6

Year Published

1997
1997
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 22 publications
5
25
2
6
Order By: Relevance
“…Performance status and the development of a metachronous tumor were additional parameters correlated with the RR of death for absolute survival. Although limited by the retrospective nature of the study, the results presented here are in keeping with much of the data reported so far 7,9,10,12,17,27,28,32 and could well represent a valid starting point for new prospective confirmatory studies.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Performance status and the development of a metachronous tumor were additional parameters correlated with the RR of death for absolute survival. Although limited by the retrospective nature of the study, the results presented here are in keeping with much of the data reported so far 7,9,10,12,17,27,28,32 and could well represent a valid starting point for new prospective confirmatory studies.…”
Section: Discussionsupporting
confidence: 84%
“…Degree of differentiation is the most extensively investigated histopathologic parameter, 6,7,10,12,14,17,19,22,26,27,29,30,32 but only a few studies have been able to document its impact on prognosis. 6,26,29 Even in our study, degree of differentiation was significantly correlated with survival in the univarate (Table 3) but was not related with an increased RR of death in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analyses were undertaken using the stepwise Cox regression model with disease-specific survival from the diagnosis as the outcome measure. In addition to the patient delay (<3 months vs Ն3 months) and the professional delay (<6 months vs 6-12 months vs Ն12 months), the following factors that have earlier been found to be important prognostic factors in laryngeal cancer were included in the model: TNM classification, [3][4][5] site of the tumor, 3,4 age, 3 (<65 vs Ն65 years), and smoking 5,11 (yes or no). TNM stage was dichotomized as stages I-III vs stage IV, because according to Breslow's test, survival at stage IV was substantially lower than at the other stages.…”
Section: Methodsmentioning
confidence: 99%
“…2 Several studies have confirmed that stage is the most important prognostic factor. [3][4][5] The reason for a patient to be seen with an advanced stage cancer may be due to rapid tumor growth, but also the patient's delay in seeking medical advice or misdiagnosis by the primary care physician may be important. There may be no alarming early symptoms, or the patient may be ignorant or deny the malignancy and therefore postpone the decision to seek medical help.…”
mentioning
confidence: 99%
“…When regional lymph nodes are involved, however, especially those contralateral to the primary lesion, the survival rates decrease by at least 50% [9,[19][20][21]. In patients with clinical evidence of cervical lymph node involvement, treatment consists mostly of radical unilateral or bilateral neck dissection, and resection of primary tumor combined with postoperative radiotherapy [22,23].…”
Section: Discussionmentioning
confidence: 99%